Built Environment and Its Influences on Walking among Older Women: Use of Standardized Geographic Units to Define Urban Forms. (13th August 2012) - Siu, Vivian W.; Lambert, William E.; Fu, Rongwei; Hillier, Teresa A.; Bosworth, Mark; Michael, Yvonne L.
Abstract : Consensus is lacking on specific and policy-relevant measures of neighborhood attributes that may affect health outcomes. To address this limitation, we created small standardized geographic units measuring the transit, commercial, and park area access, intersection, and population density for the Portland, Oregon metropolitan area. Cluster analysis was used to identify six unique urban forms: central city, city periphery, suburb, urban fringe with poor commercial access, urban fringe with pool park access, and satellite city. The urban form information was linkable to the detailed physical activity, health, and socio-demographic data of 2, 005 older women without the use of administrative boundaries. Evaluation of the relationship between urban forms and walking behavior indicates that older women residing in city center were more likely to walk than those living in city periphery, suburb communities, and urban fringe with poor commercial access; however, these women were not significantly more likely to walk compared to those residing in urban fringe with poor park access or satellite city. Utility of small standardized geographic units and clusters to measure and define built environment support research investigating the impact of built environment and health. The findings may inform environmental/policy interventions that shape communities and promote active living.